Guts - Telgemeier, Raina; Lamb, Braden (New York, NY : Graphix logo, an imprint of Scholastic, 2019)
"Raina wakes up one night with a terrible upset stomach. Her mom has one, too, so its probably just a bug. Raina eventually returns to school, where shes dealing with the usual highs and lows: friends, not-friends, and classmates who think the school year is just one long gross-out session. It soon becomes clear that Rainas tummy trouble isnt going away... and it coincides with her worries about food, school, and changing friendships. Whats going on?"--Provided by publisher.
Accelerated Reader
Keywords: Stress in children -- Juvenile literature; Comic books, strips, etc; Children -- Physiology; Juvenile literature; Comic books, strips, etc; Stomach -- Diseases; Juvenile literature; Comic books, strips, etc; Graphic novels; Comics (Graphic works); Autobiographical comics; Comic books, strips, etc